Limited ability to extend the digits of the human hand independently with extensor digitorum - Van Duinen, Hiske; Yu, Wei Shin; Gandevia, Simon C. (The Journal of physiology, 2009)
While the human hand has an extraordinary capacity to manipulate objects, movement of its digits is usually not completely independent. These limits have been documented for extrinsic flexor muscles, although hand skills also require selectivity for extension movements. Hence, we measured the degree of independent control of the major extrinsic extensor (extensor digitorum, ED). Subjects grasped a cylinder, with the thumb perpendicular to the fingers. Load cells were connected to the proximal phalanges of the fingers and the thumb's distal phalanx. Intramuscular recordings using needle electrodes were made from the individual digital compartments of ED. Subjects were instructed to extend each digit isometrically in a voluntary ramp contraction to 50% maximal force. In total, the behaviour of 283 single motor units was analysed. More than half of the units associated with one âtest' finger were recruited inadvertently when another digit contracted to 50% maximum, with most units being recruited by extension of the adjacent digits. Usually, test motor units were recruited at higher forces by extension of fingers further from the test finger. Unexpectedly, extension of the thumb recruited many motor units acting on the little finger. Across tasks, at recruitment of the test motor units, the force produced by the test finger often differed between the voluntary and inadvertent contractions. Overall, the independent control of the output of ED is limited; this may reflect âspill-over' of motor commands to other digital extensor compartments. This level of control of the extrinsic extensor muscles is more independent than the control of the deep extrinsic flexor muscle but less independent than that of the superficial extrinsic flexor muscle.